2014
DOI: 10.1007/s12020-014-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of impact of steroid replacement treatment on bone health in children with 21-hydroxylase deficiency

Abstract: There are conflicting data regarding the potential impact of chronic glucocorticoid (GC) therapy on the bone mineral density of patients with congenital adrenal hyperplasia (CAH). Previous studies performed by dual-energy X-ray absorptiometry reported conflicting results. The purpose of this study was to assess the impact of chronic GC replacement treatment in children with classical and non classical CAH due to 21-hydroxylase deficiency (21-OHD) by quantitative ultrasonometry (QUS), an easy, cheap, and radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, although DXA is the gold standard for osteoporosis diagnosis, numerous studies have demonstrated the efficiency of QUS in the screening and the early diagnosis of osteoporosis [ 49 , 50 , 51 ]. Furthermore, QUS and DXA parameters correlate between them [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although DXA is the gold standard for osteoporosis diagnosis, numerous studies have demonstrated the efficiency of QUS in the screening and the early diagnosis of osteoporosis [ 49 , 50 , 51 ]. Furthermore, QUS and DXA parameters correlate between them [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased bone mineral density and more fractures have been shown in some studies of CAH, but was absent in others [172][173][174][175][176][177][178]. Bone mineral density and fractures in patients with P30L mutations have not been studied in detail.…”
Section: Bone Healthmentioning
confidence: 99%
“…In addition, these studies showed inconsistent findings between bone mineral density (BMD), disease duration, glucocorticoid type and daily dose. The few studies regarding the skeletal health of adult CAH patients also showed controversial findings: some reported no significant differences in BMD between patients with CAH and controls, whereas others found reduced BMD in all or some subpopulations of CAH patients, for example in post‐menopausal CAH women . The inconsistent findings of these studies may be related to heterogeneous populations especially with respect to age and glucocorticoid regimes, and different methods evaluating BMD.…”
Section: Introductionmentioning
confidence: 99%